2020
DOI: 10.1073/pnas.1922622117
|View full text |Cite
|
Sign up to set email alerts
|

Pan-cancer analysis identifies mutations in SUGP1 that recapitulate mutant SF3B1 splicing dysregulation

Abstract: The gene encoding the core spliceosomal protein SF3B1 is the most frequently mutated gene encoding a splicing factor in a variety of hematologic malignancies and solid tumors. SF3B1 mutations induce use of cryptic 3′ splice sites (3′ss), and these splicing errors contribute to tumorigenesis. However, it is unclear how widespread this type of cryptic 3′ss usage is in cancers and what is the full spectrum of genetic mutations that cause such missplicing. To address this issue, we performed an unbiased pan-cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 27 publications
5
37
0
Order By: Relevance
“…Our work not only confirms the results of Zhang et al [22] and Liu et al [32], but also extends them by demonstrating no detectable difference between SF3B1 mut and SUGP1 alt splice aberration patterns in cancers and in cellular models. We strengthen that only mutations with LOH are associated with 3′ss aberrant phenotype.…”
Section: Resultssupporting
confidence: 92%
“…Our work not only confirms the results of Zhang et al [22] and Liu et al [32], but also extends them by demonstrating no detectable difference between SF3B1 mut and SUGP1 alt splice aberration patterns in cancers and in cellular models. We strengthen that only mutations with LOH are associated with 3′ss aberrant phenotype.…”
Section: Resultssupporting
confidence: 92%
“…SUGP1 (SURP And G-patch domain-containing protein, a member of the SURP family of splicing factors that likely interact with SF1 and RNA helicases) is also greatly reduced in samples from MDS patient harboring SF3B1 mutation [ 53 , 105 107 ]. Furthermore, loss or weakening of the interaction of SUGP1 with SF3B1 in the spliceosome was found to be the sole cause of defects in BP recognition, which results in the use of cryptic 3′ ss typically located 10–30 nt upstream of canonical 3′ ss [ 53 ].…”
Section: Functional Consequences Of Sf3b1 Mutationmentioning
confidence: 99%
“…Indeed, what other changes to the spliceosome cause DYNLL1 alternative-splicing is unknown. Recent work shows that loss of the splicing factor SUGP1 largely mimics the effects of SF3B1 hotspot mutations, suggesting an alternate mechanism that could affect DYNLL1 (47,48). Whether other Previous work has found that cancer-associated mutations of SF3B1 and other splicing factors cause R-loop accumulation and associated genome instability (29,31).…”
Section: Perspectivementioning
confidence: 99%